(untitled) (Pakistan Journal of Science, 2022)
This trial was designed with the objectives to select best and economical feeding strategies to accelerate growth pattern for reducing age at maturity in buffalo heifers. Twenty Sahiwal heifers (Age = 24 ± 2-month and wt. = 200 ± 30 kg) were divided into four equal groups(n-5) on the basis completely randomized design, Control group (D) of heifers was fed on green fodder only and no ration was offered while test diets were comprised on TMR based on wheat straw (A), fodder(B) and silage(C) with crude protein 10-11 percent. Feed intake of each experimental animal were recorded daily. Animals were weighed at the start of experiment and fortnightly thereafter. Animals of group C gained higher body weight (averaged 580 grams daily) comparing with other groups while animals of group (D)fed on fodder only yielded very poorly growth. Dry Matter Intakes of all groups were similar and there was no effect of treatment of different plans of diet fed to animals. Dry matter, Crude protein and crude fiber digestibility values were higher in animals fed total mixed ration based on corn silage and dry ration as compared to those fed other diets. Blood urea nitrogen values were higher in group A fed on TMR wheat straw based diet while blood glucose values were higher in animals of group B and C fed corn silage or green fodder based diet as indicator for availability of nutrients for growth.